Employee Performance Is Influenced By Flexible Time, Work Environment, And Leadership Style - Tri Wahju Wirjawan; Wachid Hasyim (Proceeding International Pelita Bangsa, 2023)
This study aims to determine how employee performance is affected by flexible time, work environment and leadership style either partially or simultaneously at PT. Y-Tec Autoparts Indonesia. Several factors that are considered to influence an employee's performance are flexible time, work environment and leadership style. The sampling method used is nonprobability sampling, namely saturated sampling technique or population research. The samples in this study were 41 male employees and 6 female employees at PT. Y-Tec Autoparts Indonesia. This study uses a multiple linear regression model with the help of the SPSS statistical program which is used to test the validity and reliability of the instrument, test the basic assumptions and classical assumptions, and test the research hypothesis. The multiple linear regression model used in this study wants to prove whether all the hypotheses proposed will be proven, namely: 1) there is a positive influence of leadership style on employee performance, 1) there is a positive effect of flexible time on employee performance, 2) there is a positive influence of work environment on employee performance, 3) there is a positive influence of leadership style on employee performance on employee performance at PT. Y-Tec Autoparts Indonesia